THE INFLUENCE OF AFFILIATE LIVE STREAMING ON SHOPEE IN CONSUMER BUYING INTEREST - Ludiana, Dina; Prasojo, Bayu Hari; Racmadany, Andry; Pebrianggara , Alshaf (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: This study aims to determine the effect of live streaming affiliates at shopee in consumer buying interest to see how Live Streaming and Affiliate Marketing have an impact on Consumer Purchase Interest at Shopee. Method: The method used in this research is quantitative descriptive method, by distributing questionnaires and processing dala in this study using the Partial Least Square (PLS) method. Results: The results showed that live streaming and affiliate marketing have a positive influence on consumer buying interest, but this influence is not statistically significant. This suggests that both strategies need to be further optimised to have a greater impact on customer purchasing decisions. Novelty: The study examines the specific role of live streaming and affiliate marketing on Shopee—a combination of digital strategies not yet extensively studied together in the context of consumer purchase interest—offering new insights into the nuanced impact of these tools on online shopping behavior.